Social Well-Being under the Engel’s Law Paradox: An Institutional Analysis Based on Sociological Research in the Republic of Tuva - Anisimova, Tatiana G.; Kubyakin, Evgeny O.; Plotnikov, Vladimir V. (The New Research of Tuva, 2026)
The article examines the phenomenon of social well-being of the population of the Republic of Tuva in the context of the Engel’s law paradox—a situation in which a high share of expenditures on basic needs (an indicator of poverty according to Engel’s law) coexists with a relatively positive subjective perception of life. The study explains why, despite low objective indicators of living standards (high poverty rates and low incomes), the surveyed sample demonstrates a comparatively high level of life satisfaction. Within an institutional framework, the analysis draws on data from sociological surveys conducted in the republic in 2021 () and 2025 (), as well as statistical indicators (poverty rates and the structure of Tuva’s economy). It is shown that most respondents positively assess their lives and are adapted to conditions of low material provision, which contradicts expectations derived from Engel’s law. The results include distributions of respondents’ incomes and self-assessments, as well as indicators of social sentiment (social well-being). The discussion focuses on institutional factors: traditional ways of life and family ties, state support (social benefits), and limited material consumption “standards,” which together mitigate the negative impact of poverty on subjective well-being. Despite the generally positive social well-being, vulnerable groups are identified (for example, women more often report feelings of loneliness and anxiety). The article emphasizes the importance of a comprehensive consideration of both objective and subjective indicators of quality of life and formulates recommendations for strengthening institutions aimed at improving living standards in the region without compromising social well-being.